Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Budaya Organisasi terhadap Kinerja Karyawan pada Bank Muamalat Indonesia Cabang Surakarta - Agus Marimin (IAIN Salatiga, 2011)
Human resource represent the key factor go to the success, along of human resource activator in operational company. The purpose if this research is to prove the influence of leadership style, work motivation, and organization culture toward employee performance of Bank Muamalat branch Indonesia Surakarta. The method used in this research is survey which using questioner for getting data. The respondents of this research are all of employee at Bank Muamalat branch Indonesia Surakarta. The data that get in this research is processed with program SPSS version 16.00. The test is done with linear regression model, t test, f test, R2 and Classic Assumption. Conclusion of this research is there is influence which significance of among leadership style, motivation, and organization culture toward employee performance of Bank Muamalat branch Indonesia Surakarta as individually.